Case Report: Canine Toxication Food Allergic - Haryo, Albiruni (Universitas Airlangga, 2019)
Canine allergies has a most common symptoms occur as skin irritations : itching, scratching, digging, and gnawing at the skin, often to the point of creating open raw wounds over large areas of the body. For the confirmation diagnosis, the patient has to be checked by laboratories examination. Based on anamneses, clinical examination and laboratories, it is logical to conclude that this dog which names choky suffers toxic allergic because of toxic accumulation from his food and the prognose was fausta. The treatments which were given for the dog are changing dog food, reducing the total protein in food at least one week, dietic protein and increasing exercise, also scalling for decreasing the plack in dog teeth. Moreover, Choky was given transfer factor supplement and antihistamin with low dosage.